Analysis Of Violations Of The Maxim Of Cooperation In The Youtube Channel Of Lost Youth (Buying Cheetahs So That Then The End Will Ride Cheetahs): A Pragmatic Study - Hidayatul Khasanah; Syahranie Mulya Winanti; Desy Prasetyaningsih; Eva Setyorini; Asep Purwo Yudi Utomo; Eva Wulandari; Rossi Galih Kesuma (International Journal of Multilingual Education and Applied Linguistics, 2024)
The principle of cooperation is definitely needed in a conversation, because with this principle, speakers and interlocutors can communicate cooperatively. Apart from helping speakers and speech partners achieve common goals in conversation, the maxim of cooperation can also provide a framework for communication to be more efficient and effective, so that it can benefit speakers and speech partners. However, sometimes in a conversation, violations arise from the speaker or speech partner involved and result in a violation of the principle of cooperation. Violations in the principle of cooperation in a speech can cause information defects and give rise to disagreements between the speaker and the speech partner. Therefore, this research was carried out with the aim of determining and explaining the types of violations of the principle of cooperation in conversations on the content of Lost Youth: "Butchering Cheetahs So that Cheetahs Will Ride in the Afterlife". This research uses pragmatic theoretical methods as well as qualitative descriptive methodological approaches. Collection techniques. The data used is a note-taking technique, namely by watching the video again, then taking notes on conversations that contain violations of the maxim of cooperation. The results of the research show that violations of the principle of cooperation that occur in the content are dominated by violations of the maxim of quantity which is characterized by the discovery of 10 violations of data. , 4 data violations of the maxim of quality, 5 data violations of the maxim of manner, and no violations of the maxim of relevance were found.